Euro area economic growth between 2010 and 2019 in the light of secular stagnation theory - Tatay, Tibor; Kazinczy, Eszter (Public Finance Quarterly, 2023)
Achieving economic growth remains an important issue for economic policy today. Growth in developed economies has slowed considerably in recent decades. In our study, we examine economic growth in the euro area between 2010 and 2019 in the light of secular stagnation theory. The concept of secular stagnation was developed by Hansen after the Great Depression of 1929-33. According to this theory, the cauSes of secular stagnation are low population growth and weak technological development. The concept was brought back into the economic discourse after 2010 by Summers. Following the 2008 crisis, euro area economies should have adjusted to a higher growth rate. Instead, growth remained below 2% for all but one year, below potential output for most of the decade. Investment rates have barely risen despite euro interest rates falling to near zero. The euro areas population barely grew despite a net migration surplus, putting a brake on employment growth. The available data suggest that neither employment growth nor productivity growth have boosted economic growth. The low level of economic growth and the evolution of the underlying factors are consistent with the theoretical assumptions described by Hansen and his followers.